MARGINALIZATION OF PARWA LEATHER PUPPET IN GIANYAR REGENCY IN GLOBALIZATION ERA - Yudabakti, I Made (E-Journal of Cultural Studies; Volume 6, Number 3, November 2013, 2013)
This present study discussed the marginalization of the Parwa Leather Puppet in Gianyar Regency in the globalization era. It discussed the form, the causing factors, and the impact of marginalization. The qualitative interpretative method was used to analyze the problems of the study. The data were collected using the techniques of observation, in-depth interview, documentary study, and library research. The data were qualitatively analyzed. The results of the study showed that there were several forms of marginalization occurring to the Parwa Leather Puppet ‘Wayang Kulit Parwa’ (WKP) in Gianyar Regency. This was indicated by the change in the context of performance and indication of marginalization. The forms of the context of performance were made up of the facts that (a) the viewers shifted from the young generation to the old generation; (b) it used to be performed as an offering but now it was performed as a commodity or comodification; (c) technology played more important roles (the lighting, sound system, and the material for making the puppet), and d) the accompanying gamelan orchestra changed. Marginalization was indicated by (a) the fall in the frequency of performance, (b) WKP was getting less popular in the community; (c) fewer people were getting interested in WKP performance; and (e) WKP was getting less respected. The factors responsible for the marginalization of WKP in Gianyar Regency were the facts that less people were interested in WKP, the decrease in the WKP puppeteer’s activities, the policy issued by the traditional institution was weak, and the supervision made by the local government of Gianyar was weak. In addition, WKP was less prospective; the current community needed more amusement than guidance, the rise in the impact of foreign cultural art, more and more sources of modern amusements were made available, and the impact of telecommunication technology. The marginalization of WKP in Gianyar Regency led to impacts and meanings. One of the impacts was that the puppeteers showed their resistances through creative, defensive, creative, innovative and transformative movements.
Keywords: marginalization, parwa leather puppet, globalization